Human Herpes Virus 6 (HHV-6)–associated Lymphadenitis: Pitfalls in Diagnosis in Benign and Malignant Settings. (October 2018) - Balakrishna, Jayalakshmi P.; Bhavsar, Tapan; Nicolae, Alina; Raffeld, Mark; Jaffe, Elaine S.; Pittaluga, Stefania
Abstract : Human herpes virus 6 (HHV-6) is a member of the β-herpesvirinae subfamily. Most people acquire HHV-6 primary infection early in life and reactivation may occur, most often in immunocompromised individuals, leading to various clinical manifestations. HHV-6 infected cells may be identified in lymph nodes in both reactive and neoplastic conditions. Cases were retrieved from the hematopathology consultation service archives at National Institutes of Health from 2003 to 2017 in which infection by HHV-6 had been documented by immunohistochemical stains to HHV-6 gp60/110 envelope glycoprotein. Five cases of reactive lymphadenitis and 3 cases of lymphoma; 2 angioimmunoblastic T-cell lymphoma and 1 classic Hodgkin lymphoma, positive for HHV-6 were identified. The reactive lymph nodes showed marked paracortical hyperplasia and admixed large atypical lymphoid cells exhibiting pleomorphic nuclei, vesicular chromatin, and prominent eosinophilic intranuclear inclusions. Vascular proliferation and necrosis were also present, raising suspicion of peripheral T-cell lymphoma. The 3 cases of lymphoma showed similar viral inclusions, in addition to the characteristic features diagnostic of the lymphoma. Staining for HHV-6 was positive with a membranous and Golgi pattern and was restricted to cells with evident inclusions on hematoxylin and eosin. HHV-6 infected cells were positive for CD3 and CD4. HHV-6 lymphadenitis can present with morphologic atypia creating a diagnostic pitfall for lymphoma. In such cases, careful attention to the characteristic viral inclusions can lead to immunohistochemical analysis highlighting the replicating virus. In cases of lymphoma, identification of the inclusions is key in detecting the associated infection as well as in avoiding misinterpretation of the lymphoma subtype.